2018
DOI: 10.3171/2018.5.peds17582
|View full text |Cite
|
Sign up to set email alerts
|

Currarino syndrome: repair of the dysraphic anomalies and resection of the presacral mass in a combined neurosurgical and general surgical approach

Abstract: OBJECTIVEIt is well established that Currarino syndrome (CS) may be associated with spinal dysraphism. Here, the authors report on 10 CS patients with dysraphic anomalies who had undergone a combined neurosurgical and general surgical approach to repair the dysraphic anomalies and resect the presacral mass in a single operation. They discuss the spectrum of spinal dysraphism that may coexist in CS in the context of its developmental etiology. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
11
0
7
Order By: Relevance
“…[10] Inheritance of Currarino's syndrome is autosomal dominant in familial cases, and the homeobox gene motor neuron and pancreas homeobox-1 (MNX1) is implicated in almost all familial cases and in almost 30% of sporadic cases. [2] Cearns et al reported 10 cases of CS patients with dysraphic anomalies and noticed that constipation was the most common presenting symptom (90%). It may be associated with urinary dysfunction, lower limbs weakness and/or sacral swelling.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…[10] Inheritance of Currarino's syndrome is autosomal dominant in familial cases, and the homeobox gene motor neuron and pancreas homeobox-1 (MNX1) is implicated in almost all familial cases and in almost 30% of sporadic cases. [2] Cearns et al reported 10 cases of CS patients with dysraphic anomalies and noticed that constipation was the most common presenting symptom (90%). It may be associated with urinary dysfunction, lower limbs weakness and/or sacral swelling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It may be associated with urinary dysfunction, lower limbs weakness and/or sacral swelling. [2] This association of constipation, sacral bony defect and a presacral mass, alongside with incomplete Currarino's syndrome is diagnosed later in life in only 19-20%; whereas the complete form with anal stenosis is diagnosed before the age of 10 in more than 80%. This is mainly explained by the severity of the triad in early childhood in the complete form [7].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations